Posterior fossa decompression with tonsillectomy in 104 cases of basilar impression, Chiari malformation and/or syringomyelia - José Alberto Gonçalves da Silva; Adailton Arcanjo dos Santos Jr; Luiz Ricardo Santiago Melo; Antônio Fernandes de Araújo; Giseuda Pessoa Regueira (Arquivos de Neuro-Psiquiatria)
The prime objective in the surgical treatment of basilar impression (BI), Chiari malformation (CM) and/or syringomyelia (SM) is based on the restoration of the normal cerebrospinal fluid (CSF) dynamics at the craniovertebral junction through the creation of a large artificial cisterna magna. A small suboccipital craniectomy has been emphasized to avoid caudal migration of the hindbrain structures into the vertebral canal. Nevertheless, the results showed downward migration of the hindbrain related to that type of craniectomy. The authors present, otherwise, the results of 104 cases of BI, CM and/or SM, whose surgical treatment was characterized by a large craniectomy with the patient in the sitting position, tonsillectomy, large opening of the fourth ventricle and duraplasty with creation of a large artificial cisterna magna. A significant upward migration of the posterior fossa structures was detected by postoperative magnetic resonance imaging.